Challenges of Warehouse Operations: A Case Study in Retail Supermarket - Saleheen, Ferdoush; Miraz, Mahadi Hasan; Habib, Md. Mamun; Hanafi, Zurina (International Journal of Supply Chain Management, 2014)
The research represents a case study on Bangladesh retail supermarket. The study demonstrates the intricacies of warehouse management practice. It elaborates the dynamics of retail supply chain and the spiral affects how warehouse can play a significant role. In addition to this, the study identifies external factors, market trends, and possible barriers which influence the overall performance of warehouse operation. The paper is based on secondary data that encompassed three major retail chains in Bangladesh. The paper also reveals opportunities to improve warehouse performances in terms of planning, design and operation. The authors demonstrate some recommendations for industry practitioners to achieve a higher level of productivity in warehouse management